The meaning of the disability rights movement for the professional field of social pedagogy in Iceland - Jóhannsdóttir, V.; Haraldsdóttir, F. (2022)
The Convention on the Rights of Persons with Disabilities (UNCRPD) is a landmark for the international disabled people’s independent living movement (ILM). The ILM has been a platform and a tool to resist the traditional medicalisation of disability by calling for a broader understanding where independence is no longer seen as the opposite of needing assistance. The field of social pedagogy in Iceland has evolved parallel with the paradigm shift grounded in the UNCRPD that replaces the medical model with the social and human rights models of disability. The aim of this article is to explore and interpret social pedagogues’ and disabled people’s perspectives on how the human rights principles and values embedded in the UNCRPD and independent living (IL) ideology can best be put into practice, as well as to cast a light on existing barriers and challenges. This study draws on qualitative data from two sources; the participants provided texts from a semi-structured questionnaire and public accounts written by disabled people. We utilise the five summarising principles of cultural-historical activity theory to further analyse and interpret the data. The contradictions drawn out of the findings show conflicts and structural tensions that have accumulated historically due to the massive legislative and policy shifts in disability services in past decades. The findings also indicate the need for a reconceptualisation of the object and the motive of the activity, i.e. disability-related social services, in order to embrace the principles, values and recommended practices grounded in the UNCRPD and the IL ideology.